O poder da ordem e a ordem do poder em Carl Schmitt - Batistella, Marco Antonio (2012)
It is intended in this dissertation thematize the notion of Power in the work of Carl Schmitt in order to problematize the concepto of the Political of the thesis in Power and Order that is inextricably perfect space conflictual politics. This claim is argumentative strategy to answer the following problem to be treated: if, on one hand, Carl Schmitt undertakes a relentless critique of "normativism" the liberal order so, however, does not waive the need for establishment of a normative order as is possible, however, to reconcile normativadade with a substantial political and non-liberal? In this context, proposes to tracejar two spheres systematic exposure, namely: 1) A critical part: containing a historical-conceptual exposition of the political structure to which Carl Schmitt controversially ensnares its antithetical force of argument, 2) A part-dogmatic conceptual: in which he exposes the positioning - decisionist - Carl Schmitt, and the way the author bases its claim of theoretical Political conceive as a typical scope of conflict and the exercise of power and law. To satisfy this proposal will provide the development of three chapters articulated. Therefore, we intend to develop in the first chapter the historical and philosophical assumptions of the crisis of modern rule of law in order to highlight the main theses articulated by current contractarian political thinkers who formed the so-called doctrine of modern natural law. In this scope, it is suggested that, noted some nuances unique and distinctive among leading theorists of that chain, there is the common denominator consistent in the primacy of the individual over the decision-making power of the State. In the second chapter, we intend to articulate how the proposed rules of Hans Kelsen is closely linked with the modern jusnaturalism. It is suggested from the outset that Kelsen proposes the theory under which the state reduces to the law, or the State / Force the Norm / Law. Indeed, it is argued that the Order engineered by normativism active in the Weimar Republic, in attempting to "neutral", presupposes the absence of a decision-maker, since where rationality of Law operates no voluntas, with no place, therefore, to mention both the "state of exception" as the meaning of "sovereignty" policy, except the "Sovereignty of Law." For ultimate, intended to articulate the last chapter, the design of Power schmittian the likeness of the very phenomenon constitutive condition of human life in the world, and argue that their manifestation does not cease to exist, or else do not reduce their intensity when the political relationship between the men. In view of this, we aim to address two notions instilled in indissoluble relation between Power and Order. These are the notion of "constituent power" and the principle of formal political "representation." These two notions expressed in Carl Schmitt, the way becomes apparent homogeneity of the people at the expense of pluralism of liberal order. Altogether the work of Carl Schmitt, and outlined the proposal of this dissertation, the objective is, ultimately, to understand how the author, in his defense of the Political, undertakes a justification of State and Law, light inextricable relationship between power and Order.